2008
DOI: 10.1007/s10734-008-9149-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the orientations of international students in Mexico: differences by region of origin

Abstract: This study examined the dispositions, experiences, and expectations of international students in a developing country to understand the increasing phenomenon of reverse student flows and the role of the political economy in international student mobility. Students' dispositions, experiences and expectations-referred here collectively as ''orientations''-served as the guiding framework for this study. Data were drawn from survey responses from 279 international students at universities throughout Mexico and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 21 publications
6
66
0
2
Order By: Relevance
“…Source: Higher education management information system data, (2013), DHET In order to address international students' reasons for mobility toward South Africa, this study utilized both quantitative and qualitative methods to uncover the motivations and aspirations of international students in the country. The research is based on a survey instrument that was previously utilized in the USA (Lee 2008(Lee , 2010, Mexico (Cantwell et al 2009), and South Korea (Jon et al 2014) and part of a larger study on international students in Africa. The general survey questions included demographic background characteristics (i.e., country of origin, field of study, and degree program); reasons for choosing South Africa and the enrolled institution; educational and career aspirations; perceptions and experiences in the country and institution; and aspirations to stay in the country, return home, or work elsewhere following graduation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Source: Higher education management information system data, (2013), DHET In order to address international students' reasons for mobility toward South Africa, this study utilized both quantitative and qualitative methods to uncover the motivations and aspirations of international students in the country. The research is based on a survey instrument that was previously utilized in the USA (Lee 2008(Lee , 2010, Mexico (Cantwell et al 2009), and South Korea (Jon et al 2014) and part of a larger study on international students in Africa. The general survey questions included demographic background characteristics (i.e., country of origin, field of study, and degree program); reasons for choosing South Africa and the enrolled institution; educational and career aspirations; perceptions and experiences in the country and institution; and aspirations to stay in the country, return home, or work elsewhere following graduation.…”
Section: Methodsmentioning
confidence: 99%
“…There has also been an emerging and significant body of research that differentiates educational migration from the perspective of non-Western and economically developing countries (Cantwell et al 2009;Kondakci 2011). Previous research has also shown that the motivations for and experiences of those migrating to nearby versus distant countries reportedly differ.…”
Section: Sadc 75%mentioning
confidence: 99%
See 1 more Smart Citation
“…La cinquième logique de mobilité enfin est sociale et, en partie, individuelle : dans une certaine mesure en effet, une trajectoire d'études à l'étranger relève du capital social, culturel et économique, qui prédispose inégalement les étudiants au rapport aux cultures et systèmes étrangers (Cantwell, Luca et Lee, 2009 ;Wagner, 1998). Enclenchée sur la base de motivations d'ordre personnel (suivre un conjoint par exemple), la mobilité correspond aussi, parfois, à des stratégies qui se déploient le plus souvent en dehors des dispositifs institutionnels de mobilité (ces étudiants-là ne sont pas boursiers, ni ne programment leur séjour en considération des programmes de coopération 15 ).…”
Section: Circuits Et Pôles éTrangers De Formation : Aperçu Des Dynamiunclassified
“…Des études récentes montrent que les trajectoires de formation obéissent, entre autres, aux caractéristiques du marché international de la formation et du travail scientifique, se déployant alors tant du Sud au Nord que du Nord au Sud, ou encore du Sud au Sud (Cantwell, Luca et Lee, 2009 ;Mazella, 2009). Nous faisons donc l'hypothèse que ces caractéris-tiques et ces dynamiques du marché international de la formation influent sur la circulation des étudiants.…”
Section: Introductionunclassified